ROLE OF CONSERVATION AGRICULTURE IN IMPROVING PRODUCTION WATER AND NITROGEN EFFICIENCY OF WHEAT UNDER RAINFED CONDITIONS - & et al., Othman (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The research work was conducted in Izra’a Research station, which affiliated to the General Commission for Scientific Agricultural Research (GCSAR), during the growing seasons (2016 – 2017; 2017 – 2018), in order to evaluate the response of two durum wheat verities (Douma3 and Cham5) and two bread wheat varieties (Douma4 and Cham6) to Conservation Agriculture (CA) as a full package compared with Conventional Tillage system (CT) under rainfed condition using lentils (Variety Edleb3) in the applied crop rotation. The experiment was laid according to split-split RCBD with three replications. The average of biological yield, grain yield, rainwater use efficiency and nitrogen use efficiency was significantly higher during the first growing season, under conservation agriculture in the presence of crop rotation, in the variety Douma3 (7466 kg. ha-1, and 4162kg. ha-1, 19.006 kg ha-1 mm-1, 39.62 kg N m-2respectively). The two varieties Douma3 and Cham6 are considered more responsive to conservation agriculture system in the southern region of Syria, because they recorded the highest grain yields (2561, 2385 kg ha-1 respectively) compared with the other studied varieties (Cham5 and Douma4) (1951 and 1724 kg ha-1 respectively). They also exhibited the highest values of both rainwater and nitrogen use efficiency.